O que a linguística sistêmico-funcional revela sobre os gêneros de texto em notas técnicas da área de agropecuária para uma proposta de ensino - Cocco, Cíntia Soares (2023)
This research had the objective of mapping and analyzing, through the Systemic Functional perspective (LSF) (HALLIDAY, 1989; 1994; HALLIDAY; MATTHIESSEN, 2004; 2014), the instantiations of text genres used to present the content of Technical Notes (TNs) (2020), of Farming and Cattle Raising for the integrated technical education with high school, in order to verify the socio-communicative purposes and the functions performed by these genres the in analyzed context. The study is based on SFL theoretical-methodological perspective, focusing lexicogrammar on transitivity and MOOD systems (HALLIDAY; MATTHIESSEN, 2004; 2014) and on Ideation and Conjunction discursive system (MARTIN, 1992, MARTIN; ROSE, 2007) especially in studies related to the genre approach of the Sydney Scholl (ROSE; MARTIN; 2008, ROSE; MARTIN, 2012, VEEL, 1997, COFFIN, 2006, MARTIN; ROSE, 2008, CHRISTIE; DEREWIANKA, 2008) in Technical Notes used in the process of training technicians in Farming and Cattle Raising in a public educational institution. As for the methodological approach, this research is qualitative of exploratory nature. The universe of analysis under investigation is the TNs from Research Group on Beef Production Systems and Supply Chain (NESPro). The corpus of this research is composed by 12 (twelve) texts that were produced and published in the year of 2020, which discuss issues related to beef cattle farming in its various segments. The analytical procedures of investigation were: the description of registry variables in each selected text; the description and analysis of the linguistic recurrences of functions of transitivity and MOOD systems; the description and analysis of the taxonomic relationships of Superordination and Composition, of Nuclear and Sequences relationships of activities from the Ideation discursive system; the description and analysis of internal and external conjunctions and their most relevant logical-semantic relations of the Conjunction system to identify stages and phases of the genres; the description of the Schematic Structure of Genre (SSG) to validate the communicative purpose and to identify the recurrent genres in the acquisition of farming and cattle raising knowledge and; the verification of the functions performed by this/these genre(s) for the teaching of the area in the analyzed context. In this way, in the 12 texts that make up the corpus three instantiations of macrogenres were identified. The procedural genre was the most instantiated in the texts of the corpus, with recurrence of 42% of the identified genres. The occurrence of this genre in the corpus is due to the nature of the course, since the objective is to educate a technician capable of guiding practical activities and experiments, as well as instructing future costumers. In a general way, we may affirm that the explanations (33% of the occurrences) and reports (25% of the occurrences) play the role of broadening the subject addressed. The results of this research indicate some important aspects regarding the teaching of Farming and Cattle Raising in Brazilian context and already demonstrate some characteristics of the language that may contribute to the learning process, since, by knowing the stages and phases of the genres, teachers and students can use the most diverse mechanisms for reading and writing texts that build learning in this area of study.